Fuzzy Comprehensive Evaluation Software of Teaching Quality Based on Entropy - Guihua Zheng; Quanlong Guan (Institute of Advanced Engineering and Science, 2013)
The present teaching evaluation models are researched on and the evaluation criteria is designed automatically from the perspectives of experts and students. And then that is made to be a kind of scientific and reasonable criteria. By combining the approach weighted entropy and fuzzy comprehensive evaluation, the present model proposes a teaching comprehensive evaluation model. This software model solves some problems in conducting quantitative analysis of teaching equality. And at the same time, it avoids subjectivity in directly assigning weight to the results. A case study shows that this software model can improve fuzzy comprehensive evaluation with reliability, accuracy as well as objectivity. The model will be suggested to optimize teaching management and improve teaching quality. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2209